Bone Cements in Depressed Frontal Bone Fractures - Meyyappan, Alagappan (Ann Maxillofac Surg, 2019)
Skull fractures can be classified into four major types; linear, depressed, diastatic, and basilar. Of these, a depressed skull fracture presents a high risk of increased intracranial pressure or hemorrhage to the brain. A compound depressed skull fracture results when a laceration over the fracture exposes the internal cranial cavity to the outside environment. Such depressed skull fractures are indicated for elevation if the defect is more than 10 mm and in the presence of brain injury. Frontal bone contour defects result in marked facial deformity which becomes obvious to the observer. Esthetic correction of the depressed frontal bone fracture can be done with autogenous bone grafts or alloplastic materials. Autogenous bone grafts are meant to be the gold standard method of reconstruction, but they harbor the risk of donor-site morbidity. There are various materials available for the reconstruction of depressed frontal bone fractures. This is a case report which illustrates the use of easily injectable, self-setting calcium phosphate bone cement in the correction of a depressed frontal bone fracture measuring approximately 3 cm × 2.5 cm × 1.5 cm.